The Ties that Bind and Blind: Embeddedness and Radicalisation of Youth in One Islamist Organisation in Pakistan. Issue 1 (2nd January 2016) - Ahmad, Akhlaq
Abstract : This article explains the factors that contributed to the socialisation of youth into a radical ideology in one nationally powerful Islamist organisation in Pakistan. It argues that young individuals who join Islamist organisations do not necessarily hold pre-existing extremist views that dispose them towards such organisations. Instead, the radicalisation of personal beliefs and worldview may in fact also occur after joining such an organisation. Findings indicate that young members' gradual orientation to an Islamist ideology resulted from the interplay of a number of factors. First, their close and significant friendships increasingly became concentrated inside the organisation. Second, participation in various organisational meetings brought a personally meaningful improvement in their skills and self-esteem. Third, the organisation bestowed power and influence on its members, both in psychological and actual terms.